2023
DOI: 10.2807/1560-7917.es.2023.28.11.2200114
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires’ disease in the EU/EEA*: increasing trend from 2017 to 2019

Abstract: Background The burden of Legionnaires’ disease (LD) in the European Union/European Economic Area (EU/EEA) has increased during the last decade, with notification rates increasing from 1.2 to 1.4/100,000 population in 2012–16, to 1.8–2.2 within 2017–19. Aim To measure weekly excess cases during 2017–19 based on previous trends and determine whether a significant change in trend occurred, and to examine any differences in age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…LD may be a cause of severe hospital-acquired pneumonia [ 21 ] but there is no evidence to suggest a role in aspiration pneumonia [ 22 ]. In temperate climates, most LD cases occur from late spring to early autumn [ 23 , 24 ], but in tropical regions they may be recorded throughout the year [ 25 ]. A general increase in incidence has been observed in Europe, the US, Canada and Australia in recent years [ 24 , 26 , 27 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…LD may be a cause of severe hospital-acquired pneumonia [ 21 ] but there is no evidence to suggest a role in aspiration pneumonia [ 22 ]. In temperate climates, most LD cases occur from late spring to early autumn [ 23 , 24 ], but in tropical regions they may be recorded throughout the year [ 25 ]. A general increase in incidence has been observed in Europe, the US, Canada and Australia in recent years [ 24 , 26 , 27 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…In temperate climates, most LD cases occur from late spring to early autumn [ 23 , 24 ], but in tropical regions they may be recorded throughout the year [ 25 ]. A general increase in incidence has been observed in Europe, the US, Canada and Australia in recent years [ 24 , 26 , 27 ]. The reasons for this worldwide increase are not totally elucidated, but it is most pronounced in older age groups (> 60 years) and with a general accentuation of seasonal trends, without any systematic changes in the methods used for its diagnosis in Europe [ 24 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, data from the European Union/European Economic Area (EU/EEA) has shown an upward trend in the notification rate for Legionella disease. This rate increased from 1.2 to 1.4/100,000 population between 2012 and 2016, and further increased to 1.8-2.2 during 2017-2019 (2). Given the limited awareness about the disease among clinicians and the difficulty of early diagnosis, the actual incidence of LP is likely higher.…”
Section: Introductionmentioning
confidence: 99%
“…Lp is also able to colonise and replicate within various phagocytic cells including human alveolar macrophages, resulting in a severe pneumonia known as Legionnaires’ disease. Immunocompromised and elderly individuals are especially susceptible to infection ( Samuelsson et al., 2023 ) and treatment failure is a serious issue as infections have a 5-10% mortality rate ( Herwaldt and Marra, 2018 ). Studies into antibiotic resistance in Lp demonstrated that in vitro evolution can lead to the emergence of macrolide-resistant clones carrying mutations in 23S RNA and ribosomal proteins L4 and L22 ( Herwaldt and Marra, 2018 ).…”
Section: Introductionmentioning
confidence: 99%